Midbody Remnant Inheritance Is Regulated by the ESCRT Subunit CHMP4C - Javier Casares-Arias; María Ujué González; Alvaro San Paulo; Leandro N. Ventimiglia; Jessica B.A. Sadler; David G. Miguez; Leticia Labat-de-Hoz; Armando Rubio-Ramos; Laura Rangel; Miguel Bernabé-Rubio; Jaime Fernández-Barrera; Isabel Correas; et al. (iScience, 2020)
Summary: The inheritance of the midbody remnant (MBR) breaks the symmetry of the two daughter cells, with functional consequences for lumen and primary cilium formation by polarized epithelial cells, and also for development and differentiation. However, despite its importance, neither the relationship between the plasma membrane and the inherited MBR nor the mechanism of MBR inheritance is well known. Here, the analysis by correlative light and ultra-high-resolution scanning electron microscopy reveals a membranous stalk that physically connects the MBR to the apical membrane of epithelial cells. The stalk, which derives from the uncleaved side of the midbody, concentrates the ESCRT machinery. The ESCRT CHMP4C subunit enables MBR inheritance, and its depletion dramatically reduces the percentage of ciliated cells. We demonstrate (1) that MBRs are physically connected to the plasma membrane, (2) how CHMP4C helps maintain the integrity of the connection, and (3) the functional importance of the connection.